The Role of Information and Cash Transfers on Early Childhood Development : Evidence from Nepal - Levere, Michael; Acharya, Gayatri; Bharadwaj, Prashant (World Bank, Washington, DC, 2017)
Although substantial progress has been made in combating malnutrition at the global level, chronic maternal and child malnutrition remains a serious problem in many parts of the developing world. This paper, using a randomized control trial design in Nepal, evaluates a program that provided information on best practices in providing child care and cash to families in extremely poor areas with pregnant mothers and/or children below the age of 2. The analysis finds significant and sizable impacts of the information plus cash intervention on maternal knowledge, behavior, child development, and nutrition. The sizes of these impacts along some measures of knowledge and development are significantly different from the information-only intervention group, suggesting a potential role for providing a short-term cash safety net along with information to tackle the problem of malnutrition.